Body mass index modified the effectiveness of low dose aspirin treatment on frozen-thawed embryo transfer outcome: a propensity score-matched study - Chen, Kaijie; Cai, Jiali; Tong, Jie; Liu, Lanlan; Liu, Zhenfang; Chen, Jinhua; Yang, Xiaolian; Yang, Chao; Geng, Jie; Ma, Caihui; Ren, Jianzhi; Jiang, Xiaoming (Frontiers in Endocrinology, 2024)
Background: Low-dose aspirin is one of the widely used adjuvants in assisted reproductive technologies with the hope of improving the live birth rate. However, the studies regarding its effects are conflicting. The study aimed to investigate the association between aspirin administration and live birth following frozen-thawed embryo transfer (FET) in patients with different body mass index (BMI).Methods: A retrospective cohort study was performed on 11,993 patients receiving FET treatments. 644 of which received a low-dose aspirin (100 mg/day) during endometrial preparation until 10 weeks after transfer. Propensity score matching was performed to avoid selection biases and potential confounders.